The The Effect of Heparin Therapy on Platelet Number and Clotting Time - Pornrat Wattanakasiwich; Ryzal Perdana (Journal of Sustainability Science and Technology, 2022)
The platelet count and clotting time are typically examined in a test to determine platelet vulnerability. A normal platelet count often affects how quickly blood clots. A low platelet count will cause a prolonged clotting time, with the exception of some conditions such kidney failure, pulmonary embolism, acute CHD, haemophilia, and chronic liver disease. A normal clotting time value will be produced by a healthy platelet count. One anticoagulant drug that can be used to treat bleeding issues is heparin. In this study, patients who received heparin therapy and those who did not are contrasted in terms of platelet counts and bleeding times. This study employed an experiment to assess the platelet count and clotting time between heparin-treated individuals and patients receiving non-heparin medication. samples gathered by the process. According to the studies, patients on heparin had an average blood clotting time of 14.98 minutes as opposed to individuals not taking heparin therapy, who had an average blood clotting time of 7.43 minutes. Patients who did not receive heparin therapy had a mean platelet count of 165,250 cells/mm3, whereas those who did had a mean platelet count of 160,050 cells/mm3. The results of the study showed that there was no significant change in platelet count between patients getting heparin therapy and those receiving non-heparin therapy (sig 2-tailed: 0.311). Despite the significant variation in the value of clotting time between individuals taking heparin medication and those not (sig 2-tailed: 0.000). In this study, anticoagulants were found to have an impact on platelet quality but no impact on platelet quantity. The bleeding time examination variable should be included in future research, along with other variables, as a normal platelet count does not always translate into the same clotting time.